A política de ciclos em uma escola da rede estadual no município de Juara - MT - Brandini, Edilamar da Silva (2011)
This interpretive qualitative research, in the form of case study analyzes the political cycles in a state school from Juara-MT. Our objective is understand how a public school in the state schools in Juara, MT, reinterprets, organizes and develops pedagogical policy cycles. And we have as a major issue: How a state school education reinterprets, organizes and develops pedagogical policy cycle? Gain importance in this context, the design cycle, the curriculum and practice focused on serving the needs presented by students in the teaching-learning process. Therefore, we consider relevant to the policy cycle approach of Ball, to analyze the context of practice and context of text production. We used as resources for data analysis: the official documents of SEDUC and School, questionnaires, interviews and observation, to understand how people of this school work with the processes of change in educational policy of the educational system. Based on the studies of Ball (1994, 1998, 2001, 2002, 2005, 2004, 2006 and 2007), Mainardes (2006, 2007, 2009) and Lopes (2004, 2005) understanding that you can only understand this process if we consider the macro and micro politics. Referring to Policy Cycles, we used Mainardes (2006, 2007, 2008a, 2008b, 2009), Krug (2001, 2007, 2008a 2008b), Freitas (2003, 2004). About change and innovation, Moreira (1990), Macedo (2002), Lopes (2005), Giroux (1986), To better understand the organization of the curriculum. Pacheco (1996), Sacristan (1995), Santomé (1995), McLaren (1997), when it comes to curriculum theory and practice, among others. They are subjects of this research, the principal, the educational coordinator, two articulators teachers and 06 full teachers, the school secretary, and three parents. The data analysis shows that: Axis 1 - Educational and Organizational Structure - realize that the school has a good structure and a framework of good teachers, but lacked the organization to meet the needs of the proposal; on Axis 2 - Pedagogical Actions - we conclude that it is unclear the design of training courses and found that the Political Pedagogical Project is a mixture of school regulations and political pedagogical project; Axis 3 - Organization-Guided Curriculum - the curriculum is still disciplinary and fragmented. Some teachers perform some actions and other innovative resist change. Axis 4 - Practical Classroom - found that the practice of school teachers and teacher organizers, is still individualized and discipline, and that some are seeking innovative practices. Axis 5 - Difficulties and facilities in the Implementation of Cycles - Among the aspects that facilitated, is the flexibility of school time and teaching globalized. And those that hampered were lack of understanding and interpretation of policy cycles and lack of infrastructure in the schools.